1993
DOI: 10.1111/j.1600-051x.1993.tb00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated opsonic activity for Porphyromonas (Bacteroides) gingivalis in serum from patients with a history of destructive periodontal disease

Abstract: We have measured the opsonic capacity of serum for the phagocytosis of Porphyromonas (Bacteroides) gingivalis by polymorphonuclear leucocytes (PMN) in 35 patients with a history of destructive periodontitis and 35 matched control subjects. The serum from cases, tested at concentrations of 8% and 0.8% opsonised P. gingivalis for phagocytosis by PMN to a level significantly greater than controls (p < 0.0001 and < 0.01 respectively). IgG antibody levels to P. gingivalis whole cells estimated by ELISA were also si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Several studies have reported a predominance of serum IgG2 antibodies in response to P. gingivalis (Lopatin and Blackburn, 1992;Whitney et al ., 1992;Polak et al ., 1995;Wilton et al ., 1993). IgG2 antibodies are the primary immunoglobulin subclass produced in response to bacterial carbohydrates and LPS and lack strong complement fixation and opsonic properties.…”
Section: (B) Geneticfactorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported a predominance of serum IgG2 antibodies in response to P. gingivalis (Lopatin and Blackburn, 1992;Whitney et al ., 1992;Polak et al ., 1995;Wilton et al ., 1993). IgG2 antibodies are the primary immunoglobulin subclass produced in response to bacterial carbohydrates and LPS and lack strong complement fixation and opsonic properties.…”
Section: (B) Geneticfactorsmentioning
confidence: 99%
“…High titers of specific antibody levels to P. gingivalis (Ling et al ., 1993;Wilton et al ., 1993;Meghji et al ., 1995) and A. actinomycetemcomitans (Saito et al ., 1993;Meghji et al ., 1995;Engström et al ., 1999) have been reported in serum and gingival crevicular fluid, although many studies report conflicting results. Positive correlations between elevated IgG levels to P. gingivalis and A. actinomycetemcomitans have been shown in gingivitis associated with both puberty and adult periodontitis (Nakagawa et al ., 1994), while a negative relationship between anti-A.…”
Section: (A) B-cells Inperiodontal Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…It is mostly found in deep periodontal pockets and active sites (13,21), and elevated levels of opsonic activity to P. gingivalis have been found in the serum of patients with a history of destructive periodontal disease (42).…”
mentioning
confidence: 99%
“…However, despite this potent antibody response the host is apparently unable to clear this chronic infection. Notwithstanding this fact, Wilton et al (20) reported that sera obtained from patients with periodontal disease contain antibodies that promote opsonophagocytosis of P. gingivalis by human neutrophils.…”
mentioning
confidence: 99%